Reasoning against madness : psychiatry and the state in Rio de Janeiro, 1830-1944 - Meyer, Manuella (Rochester studies in medical history., 2017)
Examines the emergence of Brazilian psychiatry during a period of national regeneration, demonstrating how sociopolitical negotiations can shape psychiatric professionalization.